Pembentukan Karakter pada Kelompok Belajar Anak Usia Sekolah Dasar - Palupi, Fitria Hayu (Pusat Penelitian & Pengabdian Masyarakat Poltekkes Kemenkes Palu, 2020)
This community service is aimed at developing children’s character so that they are willing to caretoward their environment (social awareness), to actively involved in activities, and improve their creativity. The method used in this community service is by doing assistance and giving accompanying to school-age children who willingly join the activities for a month which is held once in a week. The accompanying is conducted through ‘Learning is Fun’ approach. The target of this community service activity is school-age students of 7 up to 10 years old who willingly join activity for a month. The results of the activity are children willingly behave and care that cover sharing together, helping others in need, and actively involving in various activities. The results of the activity are the success of this community service activity that is reflected from the activities and the enthusiasm of children who attend which are 12 school-age children. They come and join each session orderly and carry out the activities well. Based on the communication to some parents, children have started helping simple household core, such as making the bed, sweeping, and washing. This succeed can also be seen from the children’s spirit in joining each activity. This activity is expected to be able to improve character of social care in children, foster children's creativity and improve children's learning experience.